THU0445 Validation of The Contest Questionnaires To Screen for Psoriatic Arthritis in Primary Care Psoriasis Patients. (15th July 2016) - Karreman, M.C.; Weel, A.E.; van der Ven, M.; Vis, M.; Tchetverikov, I.; Wakkee, M.; Nijsten, T.E.; Hazes, J.M.; Luime, J.J.
Abstract : Background: Various screening tools have been developed and validated over the years in order to enhance early recognition of psoriatic arthritis (PsA) among psoriasis patients, but their performance remains suboptimal. In 2014 the CONTEST-group developed a new screening tool consisting of the most discriminating questions from 3 existing tools (PEST, PASE, TOPAS) which was externally validated in 2 psoriasis cohorts from dermatology. Validation in a primary care setting has yet to be performed. Objectives: To externally validate the CONTEST questionnaire in psoriasis patients in primary care. Methods: Data from the SENSOR study was used, a cross-sectional study in adult psoriasis patients with regular spells of musculoskeletal complaints from primary care. In this study, patients completed the PEST and PASE screening-questionnaires before clinical evaluation. Within CONTEST 3 TOPAS questions are used that were not included in our study. These questions were therefore replaced by similar questions: ToPAS 2A was replaced by PEST 3, ToPAS 2B by nail assessment by a dermatologist and ToPAS 7 by data from the manikin in the PEST. We calculated sensitivity, specificity and area under the curve (AUC) for the CONTEST with a cutoff of 4, as well as the CONTEST-w (weighted version, cutoff of 8) and the CONTEST-jt (including the PEST manikin, cutoff of 5). Performance was also calculated selecting the patients in the same way as the CONTEST study, i.e. only inviting patients with a positive PEST and/or PASE questionnaire for clinical evaluation. As a reference standard we used a clinical diagnosis of PsA made by a rheumatologist and enthesitis confirmed by ultrasound (presence of Power Doppler). Results from our dataset were compared with data from the development cohort and with the performance of the PEST. Results: For this analysis 473 psoriasis patients at risk for PsA were available. Compared with the development cohort sensitivity was considerably lower in our dataset (0.30–0.51) than in the development of the CONTEST (0.86). Specificity was higher in our dataset (0.75–0.87) compared with the CONTEST development (0.35–0.48). While AUCs were around 0.7 for all three versions, comparable with the AUCs found in the development of CONTEST. Comparing these results with the performance of the PEST in our population, it shows that the sensitivity is lower for the CONTEST (0.30–0.51) than for the PEST (0.68), while the specificity is slightly higher (0.75–0.87 vs 0.71). Conclusions: External validation of the CONTEST questionnaire in primary care psoriasis patients with regular spells of musculoskeletal symptoms resulted in lower sensitivity and higher specificity compared to the development cohort, while AUCs were comparable. When only selecting patients with at least one positive screeningtool, the sensitivity slightly increases while the specificity slightly decreases. However, the performance of the CONTEST questionnaires does not seem to exceed the performance of the PEST in a primary care setting. Acknowledgement: This study was financially funded by an investigator-initiated grant from Pfizer bv. Disclosure of Interest: None declared